Optimalisasi Pemanfaatan Sistem Informasi Manajemen oleh UMKM di Tengah Transformasi Digital - Putri Fharah Silvia (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The increasingly rapid development of digital technology is pushing MSMEs to adapt to change to remain competitive in the market. One strategic step that can be taken is to adopt a Management Information Sistem (SIM) to support information management, accelerate decision-making processes, and improve business efficiency. This article examines how MSMEs can optimize the use of MIS in their business activities, highlighting the benefits, challenges, and appropriate implementation strategies. The analysis shows that MSMEs' digital capabilities, human resource training, and the availability of technological infrastructure are critical components in supporting the successful optimization of MIS in the digital era.